Santoso’s Jihadism, Deradicalization, and Humanization: A Preliminary Investigation on Indonesian Terrorism - Herdi Sahrasad; Al Chaidar; Dedy Tabrani; Teuku Syahrul Ansari; Mai Dar (Institut Agama Islam Negeri Madura, 2021)
Indonesia. The rise of acts of terrorism by Santoso at that time makes the public ask: How far is the deradicalization program? Why do the various community groups become more radical and brave against the apparatus/officers who promote the deradicalization program? Humanization leads to the prevention or overcoming of intensification of conflict and escalation of violence, covering the way for human rights violations or acts of genocide. Humanization refers to a strategy designed to reduce the dynamics of conflict that are destructive and face violence, especially terrorism, as the culmination of radicalism. Indonesia is still not free from inter-religious conflict. Religion, which should be eager to spread liberation and peace for our fellow human beings, is just often breached, even disturbing the integrity of Unity in Diversity. Deradicalization also include humanization because it takes the participation of sincere and serious attention.